Azospirillum brasilense, biopolímero e fungicida na redução das manchas amarela, marrom e ferrugem na cultura do trigo - Burg, Giovane Matias (2018)
Wheat is a widely adapted cereal grown from Rio Grande do Sul to the central region of Brazil under different cultivation conditions and disease intensity. Thus, the objective of this research was to verify the efficiency of the bacterium Azospirillum brasilense, a biopolymer and the application of fungicide, in the control of foliar diseases in wheat. The field experiment was carried out at the Federal University of Santa Maria (UFSM), Santa Maria, RS. The cultivar used was Quartz, being evaluated severity, area below the disease curve, hectoliter mass, productivity and mass of a thousand grains. The experimental design was a randomized block design with four replicates per treatment according to a two-factor model (3 x 4). The factors were constituted by three levels (0, 3, 6 applications) of the fungicide Trifloxystrobin 150.0 g / L + Prothioconazole 175.0 g / L. Being the control without application of fungicide, with three applications of the chemical fungicide, carried out in the stages of full peeling, full rubber and anthesis. And for the six applications were in the full finning, stretching, issuance of flag sheet, full rubber, piercing and anthesis. In the second factor, four treatments were used: (i) control, (ii) A. brasilense, (iii) biopolymer, (iv) A. brasilense + biopolymer. The physiological evaluations were carried out at the Plant Biotechnology laboratory of the Department of Biology of UFSM, and consisted of the collection and evaluation of four plants of each of the treatments described previously. The plants were collected and evaluated at the anthesis stage. The physiological evaluations were: hydrogen peroxide (H2O2), lipid peroxidation (T-Bars), superoxide dismutase (SOD), guaiacol peroxidase (POD), chlorophyll T (CLOROT) and carotenoids (CARO). The highest grain yields were found in applications with chemical fungicides. The treatments with Azospirillum and biopolymer, associated or isolated, had no influence on the increase of productivity nor for the control of diseases. In the laboratory treatments applications had a significant difference for the variables SOD, POD, CLOROT and CARO. In SOD, the enzymatic activity was increased when the chemical fungicide treatment was applied, and for POD, activation of this enzyme was carried out both for A. brasilense and biopolymer treatments and for chemical fungicide, where these enzymes are acting as a defense mechanism of the plant. In CLOROT and CARO, the highest averages were found in the results with fungicide application, and its highest average corresponds to the highest concentration of CLOROT and CARO in the plants and causing a positive defense effect for the plant.